Theorising from the Land: House or Tipi of IR?. (July 2022) - de Leon, Justin
In 2004, Anna Agathangelou and L.H.M. Ling wrote their important intervention, entitled 'The House of IR: From Family Power Politics to the Poises of Worldism, ' that ordered various theories of International Relations within an analogy of a colonial household, calling instead for a Worldism that builds communities based on interests and support. One glaring omission from this analysis, however, is mention of indigeneity. Increasingly, in North America, the experiences of Indigenous peoples are shaping national imaginations and popular political discourses – take for instance Idle No More, the Truth and Reconciliation Commission of Canada, Standing Rock, and Mauna Kea, to name a few. These shifts seen at a national level in North America, however, are not fully reflected in the field of IR. In fact, it would be easy to conclude that the field of IR has largely ignored Indigenous lived-experience. To this, this article asks how IR theorising, practice, and pedagogy could be significantly transformed by taking seriously Indigenous experiences and knowledge? To explore this question, this article explores the two central IR concepts of power and sovereignty to illustrate how the meanings and practices of these concepts are significantly furthered by attention to Indigenous experiences, practices, and knowledge. It concludes by asserting that an Indigenous approach to IR would not only be a mechanism for incisive analysis and critique of dominant constructions within the field, but also could provide an emergent space for (re)imagining collective futures across race and difference – something sorely needed in a world of ever increasing uncertainty. Des théories issues de la terre : la maison ou le tipi des relations internationales ?